Teenager with upper gastrointestinal obstruction - keep in mind the rare causes - Livia E. Brezeanu; Oana M. Guta; Raluca M. Vlad; Anatolie Nidelcu; Mirela Pavelescu; Daniela Pacurar (Amaltea Medical Publishing House, 2019)
Introduction. Superior mesenteric artery syndrome is a rare cause of upper gastrointestinal tract obstruction. Case presentation. A 17-year-old adolescent is admitted in the Pediatrics Department of "Grigore Alexandrescu" Hospital in Bucharest in July 2018 for episodes of vomiting associated with epigastric pain. The patient started presenting persistent abdominal pain since five years before, apparently after an appendectomy. In the last year, he associated heartburn, dysgeusia, food vomiting and postprandial plenitude. A diagnosis of H. pylori acute gastritis was initially set and he received triple therapy with temporary relief. Due to chronic digestive symptoms, the adolescent presented anxiety related to food intake with extremely reduced appetite, food selectivity and lack of weight gain. The clinical examination revealed marfanoid phenotype, low weight, chest deformity, excavated abdomen, epigastric pain and clapotage. Laboratory investigations were within normal limits. Esogastroduodenal barium examination showed an important gastric stasis with an elongated stomach, dilation of the second part of the duodenum with delayed distal passage. Abdominal ultrasound revealed reduced aorto-mesenteric distance at the third part of the duodenum. Upper gastrointestinal endoscopy found barium residue in the stomach 24 hours after the contrast study and a spastic pylorus, with impossible safe duodenal passage. Abdominal computed tomography confirmed obstruction of the third part of the duodenum by vascular compression at the aorto-mesenteric angle, a specific image for superior mesenteric artery syndrome. The patient underwent laparoscopic surgery with a good outcome. Conclusions. Although a rare entity, duodenal obstruction by aorto-mesenteric clamp must be taken into account in the differential diagnosis of vomiting. An early radiologic diagnostic spares the patient of chronic digestive disease with negative impact on nutritional status and quality of life.